Effect of a common task constraint on the body, racket, and ball kinematics of the elite junior tennis serve - Reid, M.; Whiteside, D.; Gilbin, G.; Elliott, B. (Sports Biomechanics, 2013)
The development of a powerful and accurate serve is a priority for most tennis players. Various drills are proposed to enhance characteristics of the serve such as ball speed and spin, yet research has failed to address their efficacy. The aim of this study was therefore to compare the kinematics of a flat serve with that of a service drill, where the player serves from the knees in an endeavour to promote specific changes in trunk, arm, racket, and ball motion. A 22-camera 250 Hz VICON MX motion analysis system captured the trunk, arm, racket, and ball kinematics of eight high-performance junior players hitting flat serves and knee serves. Paired t-tests assessed within-group kinematic differences between the two serve conditions. Changes in ball toss, trunk, arm, and racket kinematics were a manifestation of the constraints presented by the knee serve. These changes effected an increased angle of attack of the racket but without greater frontal plane trunk rotation, which represented primary objectives of the knee serve. In sum, partial support was offered to the use of the knee serve as an intervention that promotes immediate, specific changes in trunk and racket kinematics in the service actions of elite junior players.